A Strategy on the improvement of drinking water quality standards in Korea - KIM, Kyoung Hwa (KDI School, 2023)
This paper is to improve the drinking water quality standards in Korea that can be easily understood and experienced by the public by improving the aesthetic items among the drinking water quality standards. For items that people can easily understand when drinking tap water, such as smell, taste, and turbidity, the standards are set in the drinking water quality standards, and the results are published every month. However, civil complaints increased, such as Incheon tap water overflow accident, tap water larvae, and filter foreign substances detected in tap water at home, and the public demand for clean drinking water increased. However, there is no item for foreign matters in the current drinking water quality standards, and it is replaced by odor and taste items. On the other hand, it is urgent to improve the items and terminology that can be easily perceived by the public in the drinking water quality standards. In this paper, policy trends in the drinking water field and technical, policy, social, and economic evaluations of aesthetic items for drinking water quality standards are presented, and effective improvement methods are presented. In the future, from a long-term perspective, it is necessary to regularly review the drinking water quality standards for all items and introduce clear semantic divisions and definitions that are easy for the public to understand through regular monitoring.
Thesis(Master) -- KDI School: Master of Public Management, 2023
Keywords: Water quality--Measurement--Korea (South); Water-supply--Korea (South)